2011
DOI: 10.1002/app.35387
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial microvoid formation of poly(vinyl chloride)/polyacrylonitrile blend hollow‐fiber membranes

Abstract: Poly(vinyl chloride) (PVC)/polyacrylonitrile (PAN) blend hollow-fiber membranes were prepared by a phase-inversion method with water as inner and outer coagulations. The influence of the compatibility of the two polymers on the formation of interfacial microvoids (IFMs) in the PVC/PAN blend hollow-fiber membranes was investigated by the theory of thermodynamics and examined by Fourier transform infrared spectroscopy, dynamic mechanical analysis, viscometry, and scanning electron microscopy. All of the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…1b. The wave number (cm À1 ) corresponding to the absorption of the characteristic functional groups of the polystyrene [32][33][34], PVC [35,36] and the clay [37,38] is shown in Table 3. From these values give in Table 3 it is evident that the wave number corresponding to the absorption of some of the functional groups of polystyrene (3027, 1602 and 1493 cm À1 ) or clay (3448 cm À1 ) are retained in the unfilled and the filled blend with same or somewhat reduced absorbance as also observed in Fig.…”
Section: Ftirmentioning
confidence: 99%
“…1b. The wave number (cm À1 ) corresponding to the absorption of the characteristic functional groups of the polystyrene [32][33][34], PVC [35,36] and the clay [37,38] is shown in Table 3. From these values give in Table 3 it is evident that the wave number corresponding to the absorption of some of the functional groups of polystyrene (3027, 1602 and 1493 cm À1 ) or clay (3448 cm À1 ) are retained in the unfilled and the filled blend with same or somewhat reduced absorbance as also observed in Fig.…”
Section: Ftirmentioning
confidence: 99%
“…They concluded that considering both the water permeability and antifouling properties, adding 8 wt% copolymer was the optimal condition to obtain membrane with high filtration properties. Although PVC blend membranes have been prepared and characterized in some studies, PVC/PAN [11] and PVC/polystyrene (PS) [12] are not completely compatible. In another study, Krishnamoorthy PVC/CA blend membrane and studied its rejection properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous papers, we have done some researches of blending polymer as to promote membrane's comprehensive performance. What is Desalination 353 (2014) 118-124 more important, there are interfacial microvoids formed between the polymer matrix and dispersed phase by proper stretching which would promote the membrane porosity obviously [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%